Value-Based Digital Marketing and Brand Loyalty: Evidence from Algerian Digital Consumers - Asma Hamdoune (Journal of Excellence for Economics and Management Research, 2026)
Brand loyalty is increasingly difficult to sustain in digitally saturated markets where consumers continuously compare competing value propositions online. This study examines how Value-Based Digital Marketing (VBDM) — combining personalized content, customer value proposition, relationship management, and data-driven optimization — generates brand loyalty among Algerian digital consumers.The model tests three mediated pathways through Customer Trust & Transparency, Consumer-Brand Engagement, and Consumer-Based Brand Assets, with Collectivism Orientation moderating the engagement-loyalty link. A mixed-methods design combining PLS-SEM with expert interviews was applied across five Algerian digital consumer segments.All hypotheses are confirmed: VBDM directly predicts brand loyalty, all three mediation pathways prove statistically significant, and Collectivism Orientation meaningfully moderates the engagement-loyalty relationship. The model accounts for a substantial share of variance in brand loyalty, underscoring its explanatory strength. These findings provide actionable guidance for Algerian digital brands seeking to build sustainable loyalty in a collectivist, mobile-first consumer environment.